A study of traffic congestions and its control in Klang Town Selangor - Azhar, Mohd Riza (1984)
This study investigates the problem of traffic congestion in Klang Town, one of the oldest and most significant towns in Malaysia. Using observations, surveys, and interviews with local authorities, the research identifies key causes such as narrow bridges, poor road conditions, limited parking, and weak traffic coordination. The study recommends both short-term and long-term measures, including stricter parking control, bridge widening, and construction of by-pass roads to reduce congestion. Overall, the study concludes that while infrastructure development is crucial, the issue of traffic congestion in Klang also depends heavily on the collective responsibility and discipline of motorists, local authorities, and the community to ensure an efficient, safe, and sustainable urban transport system for the future.